Optical properties of Bi2Se3: from bulk to ultrathin films. (11th November 2016) - Eddrief, M; Vidal, F; Gallas, B
Abstract: We report on the determination of the dielectric functions of Bi2 Se3 thin films and bulk material. The Bi2 Se3 thin films with thicknesses ranging from 3–54 quintuple layers (QL) were grown by molecular beam epitaxy on GaAs(1 1 1)B substrates and the optical properties were determined from spectroscopic ellipsometry in the range of 0.5 eV–6 eV. We observed five absorption bands in the bulk sample, with a strong maximum near 2 eV, which were also present in the films down to 19 QL. Reducing the number below 19 QL in the Bi2 Se3 films caused dampening and broadening of the bulk absorption bands below 2 eV, and a shift to a higher energy of the band near 2 eV. Our experimental results thus provide evidence of marked changes in the joint density of states of Bi2 Se3 below 19 QL, indicating that the whole bulk band structure is affected for the ultrathin epilayers.